(untitled) (Experimental biology, 2026)
The study aimed to identify genetic factors associated with endurance in professional wrestlers from the Republic of Kazakhstan using a genome-wide association study (GWAS). The dataset included 58 elite combat-sport athletes and 60 non-athletic controls. Genotyping was conducted on the iScan platform (Illumina) with the Infinium Global Screening Array-24. Quality control procedures in PLINK v1.9 and subsequent analyses in R (qqman) retained 296,772 SNPs after filtering for call rate, Hardy–Weinberg equilibrium, minor allele frequency, and exclusion of sex-chromosomal and mitochondrial variants. Principal component analysis showed no substantial population stratification, and the genomic inflation factor (λ = 1.02) indicated minimal confounding. At the suggestive significance level (p < 1×10⁻⁵), several loci showed differences between athletes and controls, including rs12916133, rs7765401, GSA-rs1682809, and rs4777639. These variants are located near PPEF2, SV2B, CDC37L1, and the non-coding region LOC105370982, which are genes and regulatory elements involved in calcium-dependent signaling, synaptic regulation, proteostasis, and muscular adaptation. Although none reached genome-wide significance (p < 5×10⁻⁸), the detected trends point to a contribution of regulatory and neurometabolic pathways to endurance-related traits in wrestlers. The study is limited by the moderate sample size and the need for replication in independent Kazakhstani and international cohorts. Nevertheless, the findings form a basis for personalized training strategies and future integrative multi-omics research in sports genomics.